Dietary fat and physiological determinants of plasma chylomicron remnant homoeostasis in normolipidaemic subjects: insight into atherogenic risk. Issue 3 (20th February 2017) - Irawati, Deasy; Mamo, John C. L.; Slivkoff-Clark, Karin M.; Soares, Mario J.; James, Anthony P.
Abstract: TAG depleted remnants of postprandial chylomicrons are a risk factor for atherosclerosis. Recent studies have demonstrated that in the fasted state, the majority of chylomicrons are small enough for transcytosis to arterial subendothelial space and accelerate atherogenesis. However, the size distribution of chylomicrons in the absorptive state is unclear. This study explored in normolipidaemic subjects the postprandial distribution of the chylomicron marker, apoB-48, in a TAG-rich lipoprotein plasma fraction (Svedberg flotation rate (Sf>400), in partially hydrolysed remnants (Sf 20–400) and in a TAG-deplete fraction (Sf<20), following ingestion of isoenergetic meals with either palm oil (PO), rice bran or coconut oil. Results from this study show that the majority of fasting chylomicrons are within the potentially pro-atherogenic Sf<20 fraction (70–75 %). Following the ingestion of test meals, chylomicronaemia was also principally distributed within the Sf<20 fraction. However, approximately 40 % of subjects demonstrated exaggerated postprandial lipaemia specifically in response to the SFA-rich PO meal, with a transient shift to more buoyant chylomicron fractions. The latter demonstrates that heterogeneity in the magnitude and duration of hyper-remnantaemia is dependent on both the nature of the meal fatty acids ingested and possible metabolic determinants that influence chylomicron metabolism. The study findings reiterate that fasting plasma TAG is a poor indicator of atherogenic chylomicron remnant homoeostasis and emphasises the merits of considering specifically, chylomicron remnant abundance and kinetics in the context of atherogenic risk. Few studies address the latter, despite the majority of life being spent in the postprandial and absorptive state.